2014
DOI: 10.3109/14767058.2014.927430
|View full text |Cite
|
Sign up to set email alerts
|

Combined vaginal-cesarean delivery of twins: risk factors and neonatal outcome – a single center experience

Abstract: Non-cephalic twin B at admission or following delivery of twin A poses higher risk for combined delivery. Neonatal outcome of twin B following combined delivery are comparable with those of vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…The significantly associated risk factors identified in our study for unplanned cesarean delivery were nulliparity and nonvertex presentation of twin B. The latter was consistent for both the V‐CS and the CS‐CS groups and corresponds with other recent observations demonstrating nonvertex presentation of twin B to be a risk factor for an emergency cesarean. However, most of those studies assessed only combined delivery as the primary outcome and did not relate to the risk factors of cesarean delivery of both twins during a trial of labor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The significantly associated risk factors identified in our study for unplanned cesarean delivery were nulliparity and nonvertex presentation of twin B. The latter was consistent for both the V‐CS and the CS‐CS groups and corresponds with other recent observations demonstrating nonvertex presentation of twin B to be a risk factor for an emergency cesarean. However, most of those studies assessed only combined delivery as the primary outcome and did not relate to the risk factors of cesarean delivery of both twins during a trial of labor.…”
Section: Discussionsupporting
confidence: 91%
“…As for neonatal outcomes, it seems that twin B displayed higher morbidity rates including lower Apgar scores and hypoxic ischemic encephalopathy , although the absolute numbers are small.…”
Section: Introductionmentioning
confidence: 98%
“…Other studies have reported dichorionic-diamniotic twins to have increased risk for conversion. 11 We demonstrated induction of labor to be significantly higher in the successful VD group as compared with conversion. We hypothesize this may be due to improved deliberate timing of delivery with induction of labor and higher likelihood of having a provider available who is skilled in breech deliveries and internal podalic versions as necessary.…”
Section: Discussionmentioning
confidence: 70%
“…20,22 Avirem et al found a slightly higher risk of hemorrhagic-ischemic encephalopathy in twin B who underwent conversion, however, reported comparable overall neonatal differences between groups. 11 Aviram et al did report higher rates of morbidity in twin B as compared with twin A, though they warn that the overall prevalence of adverse outcome was low; thus, caution should be taken in drawing practical implications from these results. 12 Multifetal gestations have been shown to require significantly higher health care resources and cost as compared with singleton pregnancies.…”
Section: Discussionmentioning
confidence: 98%
“…According to studies, the distribution of fetal weight in relation to gestational age varies significantly, depending on the population and the time period. There is a difference of up to 11% in the average birth weight of newborns of different populations, at a certain gestational age, while the differences are even greater, exceeding 45% for the third percentage growth curve of the populations of these newborns [68][69][70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%